1995
DOI: 10.1074/jbc.270.34.19791
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Apolipoprotein E4 on Neurite Outgrowth Is Associated with Microtubule Depolymerization

Abstract: Evidence is presented for the differential effects of two isoforms of apolipoprotein (apo) E, apoE3 and apoE4, on neurite outgrowth and on the cytoskeleton of neuronal cells (Neuro-2a) in culture. In the presence of a lipid source, apoE3 enhances and apoE4 inhibits neurite outgrowth. Immunocytochemical studies demonstrate that there is a higher concentration of apoE3 than apoE4 in both the cell bodies and neurites. Cells treated with apoE4 showed fewer microtubules and a greatly reduced ratio of polymerized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
175
1
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 249 publications
(188 citation statements)
references
References 47 publications
7
175
1
5
Order By: Relevance
“…The major role of apoE in the brain is the transport of lipid components which contribute to building up the myelin sheath. 30,31,32 In-vitro and in-vivo studies have shown that the apoE isoforms differentially modulate neuritic outgrowth, sprouting and branching 63,64,65 and the apoE4 isoform has been specifically associated with microtubule depolymerisation 65 and axonal degeneration 66 thus potentially affecting WM integrity. Although these studies point to a differential role for the apoE isoforms on white matter structure, the molecular mechanisms require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The major role of apoE in the brain is the transport of lipid components which contribute to building up the myelin sheath. 30,31,32 In-vitro and in-vivo studies have shown that the apoE isoforms differentially modulate neuritic outgrowth, sprouting and branching 63,64,65 and the apoE4 isoform has been specifically associated with microtubule depolymerisation 65 and axonal degeneration 66 thus potentially affecting WM integrity. Although these studies point to a differential role for the apoE isoforms on white matter structure, the molecular mechanisms require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the critical role of apoE in brain plasticity after injury (in vivo and in vitro models) [6][7][8][9][10]. On the other hand, to date, few studies have addressed the importance of apoE during early postnatal development, although apoE mRNA has been shown to increase at birth, during suckling, and after fasting in the rat liver [11].…”
Section: Introductionmentioning
confidence: 99%
“…In neuronal cells in culture the amount of apoE4 that enters the cells is less than that of apoE3. 7 We have therefore suggested a possible mechanism for the combined risk conveyed by HSV1 and apoE-ε4: that on stress or immunosuppression, reactivation of the latent HSV1 occurs in brain (if present) and the number of cells infected by the virus, and hence the extent of damage, is greater in apoE-ε4 possessors than in those with the other alleles. 1 The lack of involvement of apoE-ε4 in HSK contrasts with its apparent role in AD and in herpes labialis.…”
Section: Figure 1 Agarose Gel Electrophoresis Of Amplified Products Amentioning
confidence: 99%